1968
DOI: 10.1121/1.1910761
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Rate of Monotic and Dichotically Alternating Clicks

Abstract: Subjects compared the apparent repetition rates of trains of dichotically alternating clicks, presented at 1–40/sec, with the apparent rates of monotic trains. All dichotic rates were underestimated, the degree of underestimation varying from a few percent at 1/sec to 35%–40% from about 7.5/sec onward. The latter rate corresponds to the switching rates producing minimal intelligibility of speech presented alternately to the two ears. Unlike the results of switched-speech experiments, however, the present resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1

Year Published

1971
1971
1994
1994

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 6 publications
1
21
1
Order By: Relevance
“…This latter result is a quantification of the observation, first reported by Axelrod, Guzy, and Diamond (1968), that the apparent repetition rate of interaural sequences is slower than that of monaural sequences. A further study undertaken by Axelrod and Powazek (1972) revealed that the difference in apparent rate between alternating and nonalternating sequences became smaller with decreasing angular separation between the alternating tones.…”
supporting
confidence: 73%
“…This latter result is a quantification of the observation, first reported by Axelrod, Guzy, and Diamond (1968), that the apparent repetition rate of interaural sequences is slower than that of monaural sequences. A further study undertaken by Axelrod and Powazek (1972) revealed that the difference in apparent rate between alternating and nonalternating sequences became smaller with decreasing angular separation between the alternating tones.…”
supporting
confidence: 73%
“…In other words, ear-alternating sound sequences have a slower subjective speed than their nonalternating counterparts have-a phenomenon first reported by Axelrod and co-workers Axelrod, Guzy, & Diamond, 1968;Guzy & Axelrod, 1972). This illusory phenomenon is probably related to what has been called "the sluggishness of the binaural system" (Moore, 1989, p. 222).…”
mentioning
confidence: 93%
“…At these repetition rates, the listener appears unable to shift attention rapidly enough back and forth between the ears to permit perception of all the presented clicks, so that the effective rate of dichotic clicks is substantially diminished. The apparent slowing of dichotic clicks has been observed in experiments using the psychophysical methods of limits and constant stimuli, in which Ss judged between successively presented monotic and dichotic trains, and in an experimen t in which Ss estimated the rates in clicks/second Axelrod, Guzy, & Diamond, 1968).…”
Section: Methodsmentioning
confidence: 99%